\frac{x^2-y^2}{2y^2} умножить на \frac{xy+y^2}{(x+y)^2}

\frac{(a+b)^3+(a-b)^3}{2ab(a^2+3b^2)} - 1

\frac{(a^2-ab+b^2)(a+b)^2(a-b)}{(a^3+b^3)(a^2-b^2)}

1

Ответы и объяснения

  • Участник Знаний
2012-09-22T17:34:48+00:00

(a+b)^3+(a-b)^3 / (2ab(a^2+3b^2)) - 1 =

=( a^3+3a^2b+3ab^2+b^3  +   a^3-3a^2b+3ab^2-b^3) /(2ab(a^2+3b^2)) - 1 =

=(2a^3+6ab^2) /(2ab(a^2+3b^2)) -(2ab(a^2+3b^2)) /(2ab(a^2+3b^2)) =

=(2a(a^2+3b^2) -2ab(a^2+3b^2)) /(2ab(a^2+3b^2)) =

=(2a-2ab)(a^2+3b^2)  /(2ab(a^2+3b^2)) = (2a-2ab) /(2ab)=2a(1-b)/(2ab)=

(1-b) / b